Comparison of body segmental kinematic characteristics between children with cerebral palsy performing sit-to-stand with and without a walker - Pathamaluk Thanapan (2014)
The study investigated how the subjects, 18 children with spastic diplegia aged 7-14 years, attained sit-to-stand (STS). The children were divided into two groups and three STS conditions: 1) those who could attain STS independently (I-STS), 2) those who could not attain STS independently (D-STS), and 3) subjects from the D-STS condition who could successfully attain STS with the walker (W-STS). The results showed that I-STS had more mean maximum horizontal location of the upper body and knee than the hip. All body segments of D-STS followed the same model as the I-STS condition, but they moved with less magnitude than I-STS. W-STS presented both pattern and magnitudes relatively similar to I-STS. Furthermore, I-STS showed the highest mean maximum horizontal and vertical velocities of body segments, when compared with the other STS conditions. W-STS performed the mean maximum horizontal and vertical linear velocities of all selected segments close to D-STS did.